Predicting the Position of the Internal Landmarks of Middle Cranial Fossa Using the Zygomatic Root: An Attempt to Simplify Its Complexity - Poonia, Deepika; Wadhwa, Surbhi; Mahajan, Anita; Mishra, Sabita (Indian Journal of Neurosurgery, 2022)
Subtemporal–extradural middle cranial fossa (MCF) surgical approach is used to access pathologies involving anterior or posterior part of the petrous bone or its apex. A reliable and precise identification of the important internal landmarks is key to a safe surgery with decreased incidence of morbidity. The zygomatic root (ZR) serves as a reliable reference guide for the surgeon when navigating through the MCF. The aim of the study is to establish an association between the extent of the ZR to the key internal foramina and bony prominences in lateral fossa of the MCF to help the neurosurgeon to safely navigate through the maze of structures of the MCF. The study demonstrates that the ZR is a reliable marker to estimate and predict the position of foramen ovale, foramen spinosum, and trigeminal fossa but not for the position of hiatus of greater petrosal nerve or the arcuate eminence. Successful localization of the foramen ovale, spinosum, and trigeminal fossa would reduce intraoperative time, ensure lesser retraction of brain, and hence reduce patient morbidity while performing surgeries on lesions of/in the internal acoustic canal, petroclival junctions, cerebellopontine angles, basilar artery, or transovale cannulation for the treatment of trigeminal neuralgia.
Keywords: middle cranial fossa approach; neuronavigation; zygomatic root